PICK THE LOCK - King, A. S., (Amy Sarig), 1970-; Kueck, Anna (New York, New York : DUTTON BOOKS, An imprint of Penguin Random House LLC, 2024)
"From two-time Michael L. Printz Award winner A.S. King, a weird and insightful new novel about a girl intent on picking the lock of her toxic family. Jane Vandermaker-Cook would like her mother back. As Jane's mother tours the world to support the family, Jane lives and goes to school in a Victorian mansion with her younger brother and their mendacious father, who confines Jane's mother to a system of pneumatic tubes whenever she's at home. And then there's weirdly ever-present Aunt Finch, Milorad the gardener, and his rat, Brutus. For Jane, this all seems normal until she gains access to the files for a lifetime of security camera videos -- her lifetime. Pick the Lock is a punk opera, a primal scream, and a portrait of a family buried in lies." -- Jacket flap
Keywords: Mothers and daughters -- Fiction; Dysfunctional families -- Fiction; Surrealism -- Fiction; Opera -- Fiction; Young adult fiction; Detective and mystery fiction